2004
DOI: 10.1002/bit.20074
|View full text |Cite
|
Sign up to set email alerts
|

Insights into adenoviral vector production kinetics in acoustic filter‐based perfusion cultures

Abstract: One of the major limitations in the production of adenoviral vectors is the reduction in cell-specific productivity observed for increasing cell density at infection in batch cultures. This observation strongly suggests some nutrient depletion and/or metabolite inhibition in the media. These limitations have been partially overcome through other feeding strategies, such as fed-batch and sequential batch operations. To improve these results, we evaluated perfusion as a strategy to increase the volumetric produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
1
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 36 publications
4
63
1
3
Order By: Relevance
“…Further applications should be processes in which changes in the physiological state are of primary importance for productivity, for example, viral vector production schemes and/or perfusion cultures. 26,69 To our knowledge, this article is the first report that interprets multifrequency permittivity measurements and the resulting b-dispersion parameters and relates them to the physiological state of mammalian cells. These measurements appeared to us as being a powerful on-line monitoring tool.…”
Section: Resultsmentioning
confidence: 98%
“…Further applications should be processes in which changes in the physiological state are of primary importance for productivity, for example, viral vector production schemes and/or perfusion cultures. 26,69 To our knowledge, this article is the first report that interprets multifrequency permittivity measurements and the resulting b-dispersion parameters and relates them to the physiological state of mammalian cells. These measurements appeared to us as being a powerful on-line monitoring tool.…”
Section: Resultsmentioning
confidence: 98%
“…Typically, transfection at 1 Â 10 6 cells/mL gives optimum levels of recombinant protein expression in our laboratory. However, it has been observed that at these high cellular densities adenovirus vector production is limited by reduced cell specific productivity (Nadeau and Kamen, 2003;Kamen and Henry, 2004;Henry et al, 2004). This so called ''cell density effect'' is believed to be either due to key nutrient depletion or inhibitor byproduct accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…The bioreactor setup was identical to the one used in a previous study [29]; similar conditions have been described earlier in detail [33]. In brief, a Chemap 3.5 L type SG bioreactor vessel (working volume 2.7 L) was equipped with probes to measure and control the temperature and dissolved oxygen (DO) at 37 • C and 40% air saturation.…”
Section: Bioreactor Culturesmentioning
confidence: 99%